Application of additive for coarsening electrolytic raw foil in coarsening of electrolytic raw foil, coarsening solution and preparation method of electrolytic copper foil
By using a specific additive on the surface of the electrolytic copper foil to generate the nano -level "copper teeth", it improves the surface area and peeling strength of the electrolytic copper foil, solve the problem of low anti -peeling strength in the existing technology, meets the transmission and covering of high -frequency signals and coverage High -stripping intensity requirements for copper plates.
Patent Information
- Application Number
- CN202411553189.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art ensures that the electrolytic copper foil has a low peel strength while ensuring low profile, making it difficult to meet the requirements of high-frequency signal transmission and high peel strength of copper clad plates.
Use 1-hydroxye ethyl-3-methyliopymole polystyrene sulfonate, 1-clone-3-methylpiopyrazole polystyrene sulfonate, polyetry 1-clone (3-hydroxyl) -3-nails Crippling raw foils such as Kimazazole chlorine salt and Gourier gum are used to generate additives to generate nano -level "copper teeth" on the surface of the electrolytic raw foil to improve the surface area and peeling strength.
The low surface roughness and high anti -stripping strength of the electrolytic copper foil are realized, and the high -frequency signal transmission requirements of PCB under 5G communication are met.
Smart Images

Figure CN119372725A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic copper foil, and in particular to the application of an additive for roughening electrolytic raw foil in roughening electrolytic raw foil, a roughening solution and a method for preparing the electrolytic copper foil. Background Art
[0002] With the development of new generation information technology industries such as 5G communications, automotive electronics, and artificial intelligence, the frequency and speed requirements for signal transmission are getting higher and higher. The "skin effect" of high-frequency signals is becoming more and more obvious, and the "standing wave" and "reflection" phenomena of signals will cause serious delays and distortions of signals. Low-profile electrolytic copper foil has become a key material to solve these problems. Its low roughness characteristics can reduce signal loss and distortion, and improve the efficiency and stability of signal transmission.
[0003] At the same time, the reduction of copper foil surface roughness will directly weaken the bonding force between it and the resin substrate, which will cause short circuit problems in the back-end products and make it difficult to meet the high peel strength requirements of copper foil for PCB. However, there is an inherent contradiction between the surface roughness of copper foil and its peeling performance: when the surface profile of copper foil tends to be extremely smooth, its specific surface area decreases accordingly, which limits the formation of a sufficient effective contact area between copper foil and resin substrate, resulting in a smaller peel strength.
[0004] The wide application of copper foil in chip packaging, flexible circuit boards and other fields has put forward strict requirements for it to have both ultra-low profile and high peel strength. In view of this, the roughening treatment technology of the copper foil surface is particularly important. It has become the key to reconcile this contradiction and solve related problems. The ultra-fine surface roughening treatment technology can increase the contact area and anchoring effect between the copper foil and the resin. In addition, the use of silane coupling technology to strengthen the chemical bonding ability between the copper foil and the resin can also enhance the peel strength between the copper foil and the resin substrate. The successful application of these two technologies is the key to ensuring that ultra-low profile electrolytic copper foil meets performance requirements in actual scenarios and overcomes technical bottlenecks.
[0005] The Chinese patent application with application publication number CN116497407A filed on July 28, 2023 discloses an ultra-low profile high peeling copper foil and its preparation method and application. Specifically, the electroplating solution is first subjected to electroplating to obtain an electrolytic raw foil, and then the electrolytic raw foil is placed in a micro-roughening solution for micro-roughening to obtain a micro-roughened copper foil, and then the micro-roughened copper foil is cured in a curing solution. After curing, it is alloyed and silanized to obtain an ultra-low profile high peeling copper foil, wherein the electroplating solution contains 65-150g / L sulfuric acid, 60-100g / L copper sulfate, and 10-30ppm chlorine. ions, sodium 3-mercapto-1-propane sulfonate, collagen and polyethylene glycol, the micro-roughening solution includes 10-40g / L copper sulfate, 80-200g / L sulfuric acid, 0.01-0.15g / L vanadate, 0.1-0.5g / L rare earth nitrate and 0.1-1.5g / L stannous salt and / or 1-3mg / L rare earth chloride; the surface roughness Rz of the prepared copper foil is ≤1μm, the peel strength of the PPO substrate is ≥0.6N / mm at 150-200℃, and the peel strength of the FR-4 substrate is ≥1.1N / mm at 150-170℃.
[0006] However, the above method still has low peeling strength while ensuring low profile of electrolytic copper foil. Summary of the invention
[0007] The purpose of the present invention is to provide an electrolytic green foil roughening additive for use in electrolytic green foil roughening to solve the problem that the existing additives have low peeling strength while ensuring low profile of electrolytic copper foil.
[0008] The second object of the present invention is to provide a roughening solution for roughening electrolytic raw foil, so as to solve the problem that the existing roughening solution has low peeling strength while ensuring low profile of electrolytic copper foil.
[0009] The third object of the present invention is to provide a method for preparing an electrolytic copper foil, so as to solve the problem that the existing preparation method has low peeling strength while ensuring a low profile of the electrolytic copper foil.
[0010] In order to solve the above technical problems, the technical solution of the application of the additive for roughening electrolytic green foil in the roughening of electrolytic green foil of the present invention is: The invention discloses an application of an additive for roughening electrolytic green foil in roughening electrolytic green foil, wherein the additive for roughening electrolytic green foil is selected from one or more of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum.
[0011] The present invention improves the prior art and provides an application of an additive for roughening electrolytic green foil in the roughening of electrolytic green foil. By introducing polyionic liquid, a large number of uniform and fine nanoscale "copper teeth" can be generated on the rough surface of the copper foil, thereby increasing the specific surface area of the copper foil surface, thereby ensuring a low profile while achieving high peel strength with the resin substrate. The obtained copper foil has the performance of low surface roughness and high peel strength, and can meet the performance requirements of high frequency, fast speed and low loss of PCB transmission under 5G communication.
[0012] The additive for roughening electrolytic raw foil provided by the present invention not only has strong thermal stability, a wide electrochemical window, negligible vapor pressure, controllable water solubility and high chemical and electrochemical stability, but also has designability and can carry out directionally design of polyionic liquid according to different roughening requirements to achieve targeted regulation of the micro-roughening morphology of the copper foil surface.
[0013] In order to further reduce the roughness of the electrolytic copper foil and improve the peel strength, preferably, the electrolytic raw foil roughening additive is selected from two or more of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum. The electrolytic copper foil prepared by using the above electrolytic raw foil roughening additive has a roughness Rz≤1.198 μm and a peel strength≥1.28 N / mm.
[0014] In order to further reduce the roughness of the electrolytic copper foil and improve the peel strength, preferably, the electrolytic raw foil roughening additive consists of two of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride, and the mass ratio of the two additives is (1.5~2): (1.5~2).
[0015] In order to further reduce the roughness of the electrolytic copper foil and improve the peel strength, preferably, the electrolytic green foil roughening additive is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, and poly-1-butyl (3-hydroxy)-3-methylimidazole chloride in a mass ratio of (1.5-2): (1.5-2): (1-1.5). The electrolytic copper foil prepared by using the above electrolytic green foil roughening additive has a roughness Rz≤1.103 μm and a peel strength≥1.30 N / mm.
[0016] In order to further reduce the roughness of the electrolytic copper foil and improve the peel strength, preferably, the electrolytic green foil roughening additive is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum in a mass ratio of (1.5-2): (1.5-2): (1-1.5): (0.5-1). The electrolytic copper foil prepared by using the above electrolytic green foil roughening additive has a roughness Rz≤1.032 μm and a peel strength≥1.39 N / mm.
[0017] The technical solution of the roughening solution for electrolytic green foil roughening of the present invention is: A roughening solution for roughening electrolytic green foil is provided. The roughening solution is formed by applying the roughening additive to a roughening mother solution. The roughening mother solution comprises CuSO4 and H2SO4. The mass concentration of the roughening additive in the roughening solution is 10-90 mg / L.
[0018] The roughening liquid for roughening electrolytic green foil provided by the present invention can generate a large number of uniform and fine nano-scale "copper teeth" on the rough surface of copper foil by adding the electrolytic green foil roughening additive into the roughening mother liquid and utilizing the polyionic liquid in the electrolytic green foil roughening additive, thereby increasing the specific surface area of the copper foil surface, thereby ensuring low profile while achieving high peeling strength between the copper foil and the resin substrate.
[0019] In order to further improve the roughening quality, preferably, the mass concentrations of CuSO4 and H2SO4 in the roughening solution are 10-20 g / L and 140-210 g / L.
[0020] The technical solution of the method for preparing electrolytic copper foil of the present invention is: A method for preparing an electrolytic copper foil comprises the following steps: (1) Electrodeposition is performed in an electroplating solution to obtain electrolytic green foil; (2) roughening the electrolytic raw foil in the roughening solution to obtain a roughened copper foil; (3) The roughened copper foil is cured, anti-oxidized, silane-coupled, and dried to obtain an electrolytic copper foil.
[0021] The electrolytic copper foil preparation method provided by the present invention is based on the preparation of electrolytic raw foil by electroplating solution. The electrolytic raw foil is roughened in a roughening solution to which an additive for roughening the electrolytic raw foil is added. A large number of uniform and fine nano-scale "copper teeth" can be generated on the rough surface of the copper foil by using the polyionic liquid in the additive for roughening the electrolytic raw foil, thereby increasing the specific surface area of the copper foil surface, thereby ensuring a low profile and achieving high peeling strength with a resin substrate; and the roughening can provide more growth sites for the solidification of the copper foil surface, and copper is rapidly electrodeposited on the copper foil surface by solidification, thereby preventing the nano-scale "copper teeth" crystal layer formed by the roughening from falling off, and improving the surface roughness, further improving the bonding force between the copper foil and the substrate, and improving the peeling resistance of the copper foil on the copper clad laminate, forming a layer of anti-oxidation film on the copper foil surface by anti-oxidation, improving the corrosion resistance and oxidation resistance of the copper foil, and further improving the peeling resistance of the copper foil on the copper clad laminate by silane coupling.
[0022] In order to further reduce the roughness of the electrolytic copper foil and improve the peel strength, preferably, the plating solution in step (1) comprises 90-100 g / L of CuSO4, 100-120 g / L of H2SO4 and 0-20 mg / L of additives, wherein the additives are composed of 1-3 mg / L of sodium polydisulfide dipropane sulfonate, 5-8 mg / L of hydroxyethyl cellulose, 3-5 mg / L of collagen, 1-2 mg / L of polyethylene glycol and 1-3 mg / L of hydrochloric acid.
[0023] In order to further improve the roughening efficiency, the temperature during the roughening treatment in step (2) is 20-30°C and the current density is 20-30 A / dm 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM morphology image of the rough surface of the electrolytic green foil prepared in Comparative Example 1; Figure 2 This is a SEM morphology of the rough surface of the electrolytic copper foil prepared by using the electrolytic raw foil roughening additive of Example 7; Figure 3 This is an AFM image of the rough surface of the electrolytic copper foil prepared using the additive for roughening the electrolytic raw foil in Example 7. DETAILED DESCRIPTION
[0025] The technical concept of the application of the electrolytic green foil roughening additive of the present invention in the electrolytic green foil roughening is as follows: The prior art is to obtain electrolytic green foil with low surface roughness by adjusting the plating solution formula when preparing electrolytic green foil, which is beneficial to subsequent roughening treatment and the uniformity of the roughening treatment effect; then by adjusting the roughening solution formula, dense, uniform and regular spherical copper nodule particles are obtained on the surface of the electrolytic green foil, and the size and distribution of the copper nodules are adjusted to increase the rough surface area of the copper foil so that the copper foil has an ultra-low profile, which is also beneficial to improve the surface roughness and increase the bonding strength between the copper foil and the substrate.
[0026] The present invention further improves the formula of the roughening solution on the basis of the electroplating solution formula. By introducing polyionic liquid into the roughening solution, a large number of uniform and fine nano-scale "copper teeth" are promoted to be generated on the surface of the electrolytic raw foil, thereby increasing the specific surface area of the copper foil surface, thereby ensuring low contour while achieving high peeling strength between the copper foil and the resin substrate.
[0027] The polyionic liquids used in the electrolytic foil roughening additive of the present invention are 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride. The molecular formulas of the three are as follows. Among them, the two polyionic liquids 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate and 1-butyl-3-methylimidazole polystyrene sulfonate were purchased from Shanghai Chengjie Chemical Co., Ltd. (1-butyl-3-methylimidazole polystyrene sulfonate, (C 16 H 22 N2O3S)n, molecular weight: 322.42n, purity: 92%; 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, (C 14 H 18 N2O4S)n, molecular weight: 310.37n, purity: 92%).
[0028] Poly 1-butyl (3-hydroxy) -3-methyl imidazole chloride is prepared in the laboratory. Poly 1-butyl (3-hydroxy) -3-methyl imidazole chloride is prepared by a ring-opening addition reaction of imidazole and epichlorohydrin in an aqueous solution. The ring-opening addition reaction is first reacted in ice water for 12 to 15 hours, and then reacted at 95 to 110°C for 7 to 9 days; the molar ratio of imidazole to epichlorohydrin is (1 to 2): (1 to 2); after the ring-opening reaction, a solid product is obtained by an anti-solvent, and the solid product is dried to obtain poly 1-butyl (3-hydroxy) -3-methyl imidazole chloride. Preferably, the ring-opening addition reaction is to drop epichlorohydrin into an imidazole aqueous solution for reaction, and the concentration of the imidazole aqueous solution is 1 to 2 mol / L.
[0029] The specific preparation method of poly 1-butyl (3-hydroxy) -3-methylimidazolium chloride is as follows: a certain volume of 1.0 mol / L imidazole aqueous solution is placed in an ice water bath, an equal amount of epichlorohydrin is slowly added dropwise to the above imidazole aqueous solution, and the mixture is continuously stirred in the ice water bath for 12 h; the above mixed solution is continuously stirred at 95 ° C for 7 days; after the reaction is completed, acetone is used as an anti-solvent to obtain a yellow solid from the above solution, and the desired polyionic liquid is prepared after vacuum drying.
[0030]
[0031] The method for preparing electrolytic copper foil provided by the present invention specifically comprises the following steps: using an iridium-plated plate as an anode and pure titanium as a cathode, and performing electrodeposition in an electroplating solution to obtain an electrolytic raw foil; then using the electrolytic raw foil as a cathode and iridium-plated titanium as an anode, and performing roughening treatment on the rough surface of the electrolytic raw foil in a roughening solution to obtain a roughened copper foil; and curing, anti-oxidation, silane coupling and drying the roughened copper foil to obtain the electrolytic copper foil.
[0032] In a specific embodiment, the electrodeposition is performed by direct current electrodeposition, the temperature during electrodeposition is 45-50°C, and the current density is 40-45 A / dm 2 .
[0033] In a specific embodiment, the electroplating solution is prepared from water, analytical pure CuSO4, commercially available H2SO4, and additives, wherein Cu 2+ The mass concentration is the mass of commercially available analytically pure anhydrous copper sulfate added to a certain volume of water. Similarly, the sulfuric acid concentration is the mass of commercially available concentrated sulfuric acid (mass fraction 98%) added to water. The additive includes hydrochloric acid, and the hydrochloric acid concentration is the mass of commercially available hydrochloric acid (mass fraction 37%) added to water.
[0034] In a specific embodiment, the electrolytic green foil is cleaned before roughening, and the cleaning is first ultrasonically cleaned in ethanol and acetone for 1 to 5 minutes respectively, and then placed in a 10 to 15 Vol.% dilute sulfuric acid solution for cleaning until the surface of the electrolytic green foil is bright, then taken out, and then the surface of the electrolytic green foil is cleaned with deionized water for 3 to 5 times to remove the sulfuric acid solution remaining on the surface.
[0035] In a specific embodiment, the curing is carried out in a curing liquid, which is composed of water and 40-50 g / L of Cu 2+ , 100~150 g / L H2SO4 composition, the curing temperature is 20~30℃, the current density is 20~30 A / dm 2 .
[0036] In a specific embodiment, the anti-oxidation is carried out in an anti-oxidation liquid, which is composed of water and 5-10 g / L Zn 2+、10~20g / L Cr 6+ , 80~120 g / L potassium pyrophosphate, the curing temperature is 40~50℃, the current density is 5~10 A / dm 2 , pH range is 10~12.
[0037] In a specific embodiment, the silane coupling is obtained by coating a silane coupling agent solution on the surface of the copper foil, wherein the silane coupling agent is selected from one or more of 3-aminopropyltriethyloxysilane (γ-APT), 3 (2,3-epoxypropyloxy)propyltrimethoxysilane (γ-GPT), and 3-methacryloxypropyltrimethoxysilane (γ-MPT); the concentration of the silane coupling agent solution is 1.0-2.0%, and the temperature during silane coupling is 25-35° C. Preferably, the silane coupling agent is -aminopropyltriethyloxysilane (γ-APT).
[0038] In a specific embodiment, the temperature during drying is 150-180°C.
[0039] The present invention is described in detail below in conjunction with specific examples. The raw materials used in the following examples are all conventional commercial products and are well known to those skilled in the art.
[0040] 1. Specific examples of the use of the additive for roughening electrolytic green foil of the present invention in roughening electrolytic green foil The application of the electrolytic green foil roughening additive of the present invention in the roughening of electrolytic green foil, and the formula composition of the electrolytic green foil roughening additive is shown in Table 1.
[0041] Table 1 The formula composition of additives for electrolytic foil roughening
[0042] The application of the electrolytic green foil roughening additive in Example 1 in electrolytic green foil roughening is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, and its addition amount in the roughening solution is 30 mg / L.
[0043] The application of the electrolytic green foil roughening additive in Example 2 in electrolytic green foil roughening is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is 1-butyl-3-methylimidazole polystyrene sulfonate, and its addition amount in the roughening solution is 30 mg / L.
[0044] The application of the electrolytic green foil roughening additive in Example 3 in electrolytic green foil roughening is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is poly 1-butyl (3-hydroxy)-3-methylimidazolium chloride, and its addition amount in the roughening solution is 20 mg / L.
[0045] The application of the electrolytic green foil roughening additive of Example 4 in electrolytic green foil roughening is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is guar gum, and the amount added to the roughening solution is 10 mg / L.
[0046] The application of the electrolytic green foil roughening additive in Example 5 in the roughening of electrolytic green foil is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate and 1-butyl-3-methylimidazole polystyrene sulfonate, and the addition amounts of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate and 1-butyl-3-methylimidazole polystyrene sulfonate in the roughening solution are 30 mg / L and 30 mg / L, respectively.
[0047] The application of the electrolytic green foil roughening additive in Example 6 in the roughening of electrolytic green foil is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride. The addition amounts of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride in the roughening solution are 30 mg / L, 30 mg / L and 20 mg / L, respectively.
[0048] The application of the electrolytic green foil roughening additive of Example 7 in the roughening of electrolytic green foil is to add the electrolytic green foil roughening additive into the roughening solution. The electrolytic green foil roughening additive used is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum. The addition amounts of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum in the roughening solution are 30 mg / L, 30 mg / L, 20 mg / L and 10 mg / L, respectively.
[0049] 2. Specific Embodiments of the Roughening Solution for Electrolytic Green Foil Roughening of the Present Invention The roughening solution for roughening electrolytic green foil of the present invention is obtained by applying the roughening additive for electrolytic green foil of any one of Examples 1-7 to the roughening mother liquor to form the roughening solution, the roughening mother liquor is prepared from analytical pure copper sulfate, sulfuric acid and water, and the roughening solution is obtained by adding the roughening additive for electrolytic green foil to the roughening mother liquor; the mass concentration of CuSO4 in the roughening solution is the mass of commercially available analytical pure anhydrous copper sulfate added to a certain volume of water, and similarly, the sulfuric acid concentration is the mass of commercially available concentrated sulfuric acid (mass fraction 98%) added to water. The formula composition of the roughening solution is shown in Table 2.
[0050] Table 2 Roughening fluid formula composition
[0051] The roughening solution for roughening electrolytic green foil in Example 8 is composed of a roughening mother solution and an electrolytic green foil roughening additive. The mass concentrations of CuSO4, H2SO4 and the electrolytic green foil roughening additive in the roughening solution are 20 g / L, 190 g / L and 30 mg / L, respectively; the electrolytic green foil roughening additive is 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate.
[0052] The roughening solution for roughening electrolytic green foil in Example 9 is composed of a roughening mother solution and an additive for roughening electrolytic green foil. The mass concentrations of CuSO4, H2SO4 and the additive for roughening electrolytic green foil in the roughening solution are 20 g / L, 190 g / L and 30 mg / L, respectively; the additive for roughening electrolytic green foil is 1-butyl-3-methylimidazole polystyrene sulfonate.
[0053] The roughening solution for roughening electrolytic green foil in Example 10 is composed of a roughening mother solution and an electrolytic green foil roughening additive. The mass concentrations of CuSO4, H2SO4 and the electrolytic green foil roughening additive in the roughening solution are 20 g / L, 190 g / L and 20 mg / L, respectively; the electrolytic green foil roughening additive is poly 1-butyl (3-hydroxy)-3-methylimidazole chloride.
[0054] The roughening solution for roughening electrolytic green foil in Example 11 is composed of a roughening mother solution and an electrolytic green foil roughening additive. The mass concentrations of CuSO4, H2SO4 and the electrolytic green foil roughening additive in the roughening solution are 20 g / L, 190 g / L and 10 mg / L, respectively; the electrolytic green foil roughening additive is guar gum.
[0055] The roughening solution for roughening electrolytic green foil in Example 12 is composed of a roughening mother solution and an additive for roughening electrolytic green foil, and the mass concentrations of CuSO4, H2SO4 and the additive for roughening electrolytic green foil in the roughening solution are 20 g / L, 190 g / L and 60 mg / L, respectively; the additive for roughening electrolytic green foil is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate and 1-butyl-3-methylimidazole polystyrene sulfonate, and the mass concentrations of the two in the roughening solution are 30 mg / L and 30 mg / L, respectively.
[0056] The roughening solution for roughening electrolytic green foil in Example 13 is composed of a roughening mother solution and an electrolytic green foil roughening additive, and the mass concentrations of CuSO4, H2SO4 and the electrolytic green foil roughening additive in the roughening solution are 20 g / L, 190 g / L and 80 mg / L, respectively; the electrolytic green foil roughening additive is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride, and the mass concentrations of the three in the roughening solution are 30 mg / L, 30 mg / L and 20 mg / L, respectively.
[0057] The roughening solution for roughening electrolytic green foil in Example 14 is composed of a roughening mother solution and an additive for roughening electrolytic green foil. The mass concentrations of CuSO4, H2SO4 and the additive for roughening electrolytic green foil in the roughening solution are 20 g / L, 190 g / L and 90 mg / L, respectively; the additive for roughening electrolytic green foil is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum. The mass concentrations of the four in the roughening solution are 30 mg / L, 30 mg / L, 20 mg / L and 10 mg / L, respectively.
[0058] 3. Specific embodiments of the method for preparing electrolytic copper foil of the present invention Embodiment 15 The preparation method of the electrolytic copper foil in this embodiment is as follows: (1) Preparation of electrolytic green foil: copper sulfate, sulfuric acid and additives were added to water to prepare an electroplating solution. The mass concentrations of CuSO4, H2SO4 and additives in the electroplating solution were 90 g / L, 100 g / L and 14 mg / L, respectively. The additives were composed of sodium polydisulfide propane sulfonate (SPS), hydroxyethyl cellulose, collagen, polyethylene glycol and hydrochloric acid. The mass concentrations of each component in the electroplating solution were 3 mg / L, 5 mg / L, 3 mg / L, 2 mg / L and 1 mg / L, respectively. An iridium-plated plate was used as the anode and pure titanium was used as the cathode. Electroplating was carried out in the electroplating solution to obtain electrolytic green foil. The temperature during electrodeposition was 45 °C and the current density was 40 A / dm 2 .
[0059] (2) Roughening treatment: Before roughening, the electrolytic green foil obtained in step (1) is cleaned, specifically: first, ultrasonically cleaned in ethanol and acetone for 1 min respectively, then placed in a 10 vol.% dilute sulfuric acid solution for cleaning until the surface of the electrolytic green foil is bright and then taken out, and then the surface of the electrolytic green foil is cleaned with deionized water for 3 to 5 times to remove the sulfuric acid solution remaining on the surface; the cleaned electrolytic green foil is used as the cathode and the iridium-plated titanium is used as the anode, and the rough surface of the electrolytic green foil is roughened in the roughening solution of any one of Examples 8 to 14 to obtain a roughened copper foil, and the temperature during the roughening treatment is 30° C. and the current density is 20 A / dm 2 .
[0060] (3) Curing: After roughening treatment, the curing treatment is carried out in a curing liquid. The curing liquid consists of water, 40 g / L CuSO4, and 130 g / L H2SO4. The curing temperature is 30°C and the current density is 20 A / dm 2 .
[0061] (4) Anti-oxidation: After curing, the anti-oxidation treatment is carried out in an anti-oxidation solution, which consists of water and 10 g / L Zn 2+ 、10g / L Cr 6+ , 120 g / L potassium pyrophosphate, the curing temperature is 40°C, the current density is 10 A / dm 2 , pH range is 10~12.
[0062] (5) Silane coupling: After the anti-oxidation treatment, a silane coupling agent solution is applied on the surface of the copper foil. The silane coupling agent is 3-aminopropyltriethyloxysilane (γ-APT). The volume concentration of the silane coupling agent solution is 1.0-2.0%. The temperature during silane coupling is 30°C. The specific method of using the silane coupling agent is as follows: 1) ethanol and water are mixed in a volume ratio of 1:1 to form a homogeneous solution; 2) the silane coupling agent is added to the above homogeneous solution of ethanol and water to make the volume concentration of the silane coupling agent 1.0-2.0%.
[0063] (6) Drying: After the silane coupling treatment is completed, the copper foil is dried at 150-180°C to obtain an electrolytic copper foil.
[0064] 4. Comparative Proportion Comparative Example 1 The method for preparing the electrolytic copper foil in this comparative example is basically the same as that in Example 15, except that only the preparation of the electrolytic raw foil in step (1) is performed, and steps (2) to (6) are not performed.
[0065] Comparative Example 2 The method for preparing the electrolytic copper foil in this comparative example is basically the same as that in Example 15, except that no additive for roughening the electrolytic raw foil is added during the roughening treatment in step (2).
[0066] V. Experimental Examples Experimental Example 1 In this experimental example, the rough surface morphology of the prepared electrolytic copper foil was characterized. Figure 1 This is a SEM morphology image of the rough surface of the electrolytic green foil prepared in Comparative Example 1; Figure 2 This is a SEM morphology of the rough surface of the electrolytic copper foil prepared by using the electrolytic raw foil roughening additive of Example 7; Figure 3 This is an AFM image of the rough surface of the electrolytic copper foil prepared using the additive for roughening the electrolytic raw foil in Example 7.
[0067] from Figure 1-3 It can be seen that by using the electrolytic raw foil roughening additive provided by the present invention, a large number of "copper teeth" are generated on the surface of the electrolytic copper foil, which can maintain a relatively low surface roughness.
[0068] Experimental Example 2 In this experimental example, the roughness Rz of the electrolytic copper foil was tested by a JD-520 roughness tester, and the peel strength Ps of the electrolytic copper foil was tested by a MK-BL-X-90 degree peel strength tester.
[0069] The specific test method is as follows: 1. Roughness test: Place the copper foil flat on the operating table, use the roughness instrument to test the copper foil three times in the horizontal and vertical directions, and take the average of the six experimental results as the test result of roughness Rz; 2. Peel strength test: Four test strips with a width of 3.0 mm were cut from the surface of the copper-clad laminate formed by pressing copper foil and FR-4 prepreg, and the test was carried out at a peeling speed of 50 mm / min and a test angle of 90±5°. The peel strength of each test strip was calculated based on the minimum load displayed by the instrument, and the average of the four experimental results was taken as the peel strength test result. The test results are shown in Table 3.
[0070] Table 3 Test results of roughness Rz and peel strength Ps of electrolytic copper foil
[0071] It can be seen from Table 3 that, compared with the electrolytic green foil (Comparative Example 1), the electrolytic green foil is roughened by using the electrolytic green foil roughening additive provided by the present invention, and although the roughness of the electrolytic copper foil obtained is increased, the peeling strength is greatly improved; and compared with the case where no electrolytic green foil roughening additive is added (Comparative Example 2), while the surface roughness of the electrolytic copper foil is reduced, the peeling strength is also greatly improved, indicating that the electrolytic green foil is roughened by using the electrolytic green foil roughening additive provided by the present invention, and a large number of uniform and fine nano-scale "copper teeth" can be generated on the surface of the electrolytic green foil, thereby increasing the specific surface area of the copper foil surface, and can reduce the roughness of the prepared electrolytic copper foil while improving the peeling strength.
[0072] In addition, compared with a single additive (Examples 1-4), the electrolytic raw foil roughening additives formed by more than two components (Examples 5-7) show lower roughness and higher peel strength, and as the number of components increases, the roughness is lower and the peel strength is higher. The roughness of the electrolytic copper foil can be as low as 1.032µm, and the peel strength reaches 1.39 N / mm.
[0073] The present invention can have other forms of embodiments according to the above preparation method, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made to the above embodiments by any technician familiar with the profession according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. Application of an additive for roughening electrolytic green foil in roughening electrolytic green foil, characterized in that: The electrolytic foil roughening additive is selected from one or more of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum.
2. Use of the electrolytic green foil roughening additive according to claim 1 in electrolytic green foil roughening, characterized in that: The electrolytic foil roughening additive is selected from two or more of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum.
3. Use of the electrolytic green foil roughening additive according to claim 1 in electrolytic green foil roughening, characterized in that: The electrolytic foil roughening additive is composed of two of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride, and the mass ratio of the two additives is (1.5-2): (1.5-2).
4. Use of the electrolytic green foil roughening additive according to claim 1 in electrolytic green foil roughening, characterized in that: The electrolytic green foil roughening additive is composed of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, and poly 1-butyl (3-hydroxy)-3-methylimidazole chloride in a mass ratio of (1.5-2): (1.5-2): (1-1.5).
5. Use of the electrolytic green foil roughening additive according to claim 1 in electrolytic green foil roughening, characterized in that: The electrolytic green foil roughening additive consists of 1-hydroxyethyl-3-methylimidazole polystyrene sulfonate, 1-butyl-3-methylimidazole polystyrene sulfonate, poly 1-butyl (3-hydroxy)-3-methylimidazole chloride and guar gum in a mass ratio of (1.5-2): (1.5-2): (1-1.5): (0.5-1).
6. A roughening solution for roughening electrolytic green foil, characterized in that: The electrolytic green foil roughening additive according to any one of claims 1 to 5 is applied to a roughening mother liquor to form a roughening solution, wherein the roughening mother liquor comprises CuSO4 and H2SO4, and the mass concentration of the electrolytic green foil roughening additive in the roughening solution is 10-90 mg / L.
7. The roughening solution for roughening electrolytic green foil according to claim 6, characterized in that: The mass concentrations of CuSO4 and H2SO4 in the coarsening solution are 10~20 g / L and 140~210 g / L.
8. A method for preparing electrolytic copper foil, characterized in that: The following steps are involved: (1) Electrodeposition is performed in an electroplating solution to obtain electrolytic green foil; (2) roughening the electrolytic raw foil in the roughening solution of claim 6 or 7 to obtain a roughened copper foil; (3) The roughened copper foil is cured, anti-oxidized, silane-coupled, and dried to obtain an electrolytic copper foil.
9. The method for preparing electrolytic copper foil according to claim 8, characterized in that: The electroplating solution in step (1) comprises 90-100 g / L of CuSO4, 100-120 g / L of H2SO4 and 0-20 mg / L of additives, wherein the additives consist of 1-3 mg / L of sodium polydisulfide dipropane sulfonate, 5-8 mg / L of hydroxyethyl cellulose, 3-5 mg / L of collagen, 1-2 mg / L of polyethylene glycol and 1-3 mg / L of hydrochloric acid.
10. The method for preparing electrolytic copper foil according to claim 8, characterized in that: The temperature during the roughening treatment in step (2) is 20-30°C, and the current density is 20-30 A / dm 2 .
Citation Information
Patent Citations
Ultralow-profile high-stripping copper foil and preparation method and application thereof
CN116497407A
Cited By
Preparation method of high-conductivity HVLP copper foil
CN121718940A
A method for manufacturing a high-conductivity hvlp copper foil
CN121718940B
A method for enhancing the thrust of a circuit board for an LED light plate
CN122970791A